2014
DOI: 10.1155/2014/231795
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Assessment of Secondary Bone Graft Outcomes in Cleft Lip and Palate Patients

Abstract: Purpose. To compare the results of secondary alveolar bone grafts in patients with complete cleft lip and cleft lip and palate using 2 radiographic scales and according to the rate of canine eruption through the newly formed bone. Materials and Methods. We analyzed pre- and postoperative radiographs of 36 patients for the amount of bone in the cleft site according to the Bergland and Chelsea scales. The associations between the variables and the correlation between the scales were measured. Results. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…It has been suggested that the timing of the SABG is a critical variable affecting its outcome [24][25][26][27][28]. Nonetheless, surprisingly few studies evaluated results of SABG performed earlier than a widely accepted age range of 8-11 years that was assumed to be optimal for clinical success since the 1970s [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the timing of the SABG is a critical variable affecting its outcome [24][25][26][27][28]. Nonetheless, surprisingly few studies evaluated results of SABG performed earlier than a widely accepted age range of 8-11 years that was assumed to be optimal for clinical success since the 1970s [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…A number of criteria for clinical evaluation of grafts have been proposed, including periodontal insertion level, adequate width of attached gingiva in the cleft vicinities, eruption of permanent central and lateral incisors (for early secondary bone grafting) and canine teeth into grafted bone, absence of exposed root structures adjacent to clefts,[ 5 ] aesthetic results conferred by bony support of alar base, closure of any existing palatal fistula,[ 6 ] and stabilisation of premaxilla in conjunction with bilateral clefting. [ 7 8 ]…”
Section: S Ubjects and M Ethodsmentioning
confidence: 99%
“…In type III, the occlusal position of the alveolar bone is between one half and three fourths of the normal height and finally type IV cases have a lower than half of the normal interdental septum height. 23 Moreover, in all of the included studies, cases with the type I and II Bergland scores were considered to be successful while the type III and IV alveolar evaluations were considered to be failures. In our review, we also compared the mean Bergland scale score between secondary alveolar bone grafts and NAM as a more accurate outcome measure than success rate.…”
Section: Summary Of Evidence and Factors Affecting The Main Outcomementioning
confidence: 99%